Feeding the Soul: Voices of Kentucky Women Combating Child Hunger - Price, Mya (Advances in Social Sciences Research Journal, 2023)
This study addresses the overarching topic of food insecurity by giving voice to individuals who dedicate their careers to combating child food insecurity throughout their communities. Voices are uplifted through the representation of narratives by volunteer coordinators overseeing child feeding programs, which have been established throughout Kentucky as an effort to help alleviate child hunger. This study is guided by London’s theory on career motivation. The outcomes of this study serve as a pilot for future research centered on individuals working to combat child food insecurity. The narratives collected from this study will be used as a resource for generating public conversation, spreading awareness, and to “tell the story “In regards to child hunger across Kentucky.